The Quora website for students in learning the skill of Arabic Reading on the Internet (an analytical and descriptive study) | موقع كورا (Quora) للطلبة في تعلم مهارة القراءة على الوسائل الانترنت (دراسة تحليلية وصفية) - Muhammad Wahyudi; Mustofa, Yusuf (UIN Raden Mas Said Surakarta, 2023)
Electronic or computerized information sources have become an important part of libraries, especially those that aim to keep pace with modern developments to keep users up to date on scientific research, seminars and conferences covering all fields. This study aims to describe the Quora site as a site for students to learn in Internet-based Arabic reading skills. This research is a type of qualitative literature study with descriptive and analytical methods. Library sources are used to obtain data for scientific research. The object of this research is the Quora site. The results showed that 1) The idea of creating a Quora site is based on the fact that most human experience, knowledge, and opinions are still not available on the Internet, but can be found in people's books and experiences; 2) Quora aims to share all the knowledge available in the world through people's contributions to this knowledge base; 3) Quora allows everyone to access it.